Effect of anatomic fibula on tibia union and alignment after intramedullary nailing of tibia shaft fractures - Evren, Ali Teoman; Yaradılmış, Yüksel Uğur; Okkaoğlu, Mustafa Caner; Ateş, Ahmet; Demirkale, İsmail; Altay, Murat (The European Research Journal, 2020)
Objectives: The effect of an intact or fixated fibula on tibial union and alignment in tibial shaft fractures applied with intramedullary nailing is investigated.Methods: A retrospective examination was made of 67 patients aged 19-85 years who were applied with intramedullary nailing for a tibial shaft fracture (AO-42) between January 2010 and December 2016. The 44 patients included in the study were separated into 2 groups as those with anatomic fibula (Group 1, n = 12) and those with a fibula fracture which is not fixated (Group 2, n = 32). The patients were evaluated in respect of bone union and malalignment from direct radiographs. Union was evaluated according to the RUST criteria, and the threshold for malalignment was taken as 5˚ in the coronal and sagittal planes.Results: The patients comprised 24 males and 20 females (M/F: 6/5) with a mean age of 42.7 years (range, 19-76 years). Non-union was observed in 3/12 patients (25%) in Group 1, and in 2/32 (6.3%) patients in Group 2 at 6 months. Malalignment was observed in 1/12 (8.3%) patients in Group 1 (procurvatum) and in 7/32 (21.8%) patients in Group 2, of which 3 (9.3%) were varus, and 4 (12.5%) were valgus. The rate of malalignment was significantly lower in Group 1 than in Group 2.Conclusions: The results demonstrated that bone union of a tibial shaft fracture is slower in patients with an anatomic fibula compared to those with non-anatomic fibula. Although the anatomic fibula slows the rate of union, it prevents malalignment.